On the Security of NMAC and Its Variants - Fanbao Liu; Changxiang Shen; Tao Xie; Dengguo Feng (Universitas Ahmad Dahlan, 2013)
Based on the three earlier MAC (Message Authentication Code) construction approaches, we propose and analyze some variants of NMAC. We propose some key recovery attacks to these NMAC variants, for example, we can recover the equivalent inner key of NMAC in about O(2n/2) MAC operations, in a related key setting. We propose NMAC-E, a variant of NMAC with secret envelop, to achieve more process efficiency and no loss of security, which needs only one call to the underlying hash function, instead of two invocations in HMAC.